Psoriasis: an emerging risk factor for ischemic stroke? - Piotr Olejnik; Kaja Kasarełło; Renata Podkowińska-Polak; Aleksandra Golenia (Frontiers in Neurology)
In 2020 nearly 12 million people worldwide suffered a stroke, and acute ischemic stroke (AIS) is the most frequent stroke subtype, accounting for approximately 65% of total stroke incidence. Therefore, primary prevention, including non-traditional risk factors, should be recognized as a major public health priority. Research has shown that autoimmune diseases associated with chronic systemic inflammation, such as psoriasis, are commonly linked to AIS incidence. Psoriasis is a chronic autoimmune erythematous-squamous disease that primarily affects the skin, nails, and joints. Psoriasis is known to be a systemic inflammatory condition affecting multiple organs. Patients with psoriasis are at a higher risk of stroke than the general population, and a more severe disease course can increase this risk by up to 44%. One possible explanation for this phenomenon is that chronic systemic inflammation is associated with endothelial dysfunction and atherosclerotic plaque development. On the other hand, patients with psoriasis have an increased prevalence of traditional cardiovascular risk factors, including metabolic syndrome. This narrative review synthesizes the scientific literature to provide a comprehensive overview of the current understanding of the association between psoriasis and AIS.